Free-standing graphene oxide/oxidized carbon nanotube films with mixed proton and electron conductor properties. (18th January 2023) - Rabin, Nurun Nahar; Islam, Md. Saidul; Rahman, Mohammad Atiqur; Tagawa, Ryuta; Shudo, Yuta; Sekine, Yoshihiro; Hayami, Shinya
Abstract : A free-standing film of graphene oxide and oxidized single-wall carbon nanotubes showing efficient mixed proton and electron conduction at room temperature is demonstrated. Abstract : Herein, a hybrid of graphene oxide and oxidized single-wall carbon nanotube (GO/Ox-SWCNT) free-standing film showing efficient mixed proton and electron conducting (MPEC) properties is demonstrated. The obtained proton and electronic conductivities are 5.24 × 10 −3 and 1.35 × 10 −3 S cm −1, respectively. The ease of the GO/Ox-SWCNT free-standing film synthesis process along with the excellent MPEC performance endow the films with a wide range of applications as solid electrolyte membranes.